Association between Hepatic Steatosis and Obstructive Sleep Apnea in Children and Adolescents with Obesity - Marco Carotenuto; Anna Di Sessa; Maria Esposito; Anna Grandone; Pierluigi Marzuillo; Ilaria Bitetti; Giuseppina Rosaria Umano; Francesco Precenzano; Emanuele Miraglia del Giudice; Nicola Santoro (MDPI AG, 2021)
Background: Owing to the increasing rate of pediatric obesity, its complications such as non-alcoholic fatty liver disease (NAFLD) and obstructive sleep apnea (OSA) have become prevalent already in childhood. We aimed to assess the relationship between these two diseases in a cohort of children with obesity. Methods: We enrolled 153 children with obesity (mean age 10.5 ± 2.66, mean BMI 30.9 ± 5.1) showing OSA. Subjects underwent a laboratory evaluation, a cardio-respiratory polysomnography (PSG), and a liver ultrasound. Results: All subjects had a clinical diagnosis of OSA based on the AHI > 1/h (mean AHI 8.0 ± 5.9; range 2.21-19.0). Of these, 69 showed hepatic steatosis (62.3% as mild, 20.3% as moderate, and 17.4% as severe degree). A strong association between ALT and apnea/hypopnea index (AHI) was observed (p = 0.0003). This association was not confirmed after adjusting for hepatic steatosis (p = 0.53). By subdividing our population according to the presence/absence of steatosis, this association was found only in the steatosis group (p = 0.009). As the severity of steatosis increased, the significance of its association with AHI compared to the absence of steatosis became progressively stronger (all p < 0.0001). Conclusions: Hepatic steatosis seems to drive the association between OSA and ALT levels, suggesting a potential pathogenic role of OSA in NAFLD.